The 5th International Conference on Semiotics of Culture & Visual Communication - Mouzouropoulos, Theseas (My University, 2024)
On November 9, the Ecuador Poster Biennial 2024 offered a cultural route through Quito's museums, highlighting 246 posters at the Metropolitan Cultural Center and 247 at the Muñoz Mariño Museum, reaffirming Quito as a center of art and visual communication. The Metropolitan Cultural Center hosted the opening of the EPB 2024 International Poster Exhibition, featuring works by global designers. The Exhibition opened at the Metropolitan Cultural Center of Quito, with an outstanding selection of posters by international artists that celebrate creativity and graphic design as a communication tool. The Muñoz Mariño Museum inaugurated the EPB 2024 International Poster Exhibition, highlighting creativity in categories E (Ecuador), A (Advertising) and C (Students).
EPB2024 Ecuador Poster Bienal
Keywords: poster design; graphic design